Comparison of the different kinematic patterns during lateral bending between subjects with and without recurrent low back pain. (October 2016) - Sung, Paul S.; Danial, Pamela; Lee, Dongchul C.
Abstract: Background: Lateral bending is a prerequisite for various functional activities of daily life, which require combined three-dimensional motion. Even though a number of studies have evaluated spinal kinematic changes during lateral bending, the literature reveals a lack of data based on limb dominance. The purpose of this study was to compare kinematic angular displacement of the spinal regions for dominant and non-dominant lateral bending in subjects with and without recurrent low back pain. Methods: Forty-four right hand dominant individuals with recurrent low back pain (43.1 [17.4] years) and without low back pain (39.7 [18.7] years) participated in this study. All participants were asked to perform trunk lateral bending to the dominant and non-dominant sides with a bar, three times repeatedly. The outcome measures included three-dimensional angular displacements for the three regions of the spine (upper thorax, lower thorax, and lumbar spine). Findings: Lumbar rotation (degrees) increased to the dominant side in the low back pain group (9.29 [1.06]) compared to the control group (6.20 [1.02]) with increased rotation in the upper thorax as well ( t = − 2.09, p = 0.04). However, the upper thorax rotation increased in the low back pain group to the non-dominant side ( t = 2.08, p = 0.03) and to the dominant side ( t = − 2.35, p = 0.02). There was a group interaction with planes (F = 5.82, p = 0.02) during lateral bending. Interpretation: Although lower thorax motion was not different between groups, increased lumbar spine and upper thorax rotations to the dominant side in the low back pain group were evident during lateral bending. This directional asymmetry should be carefully monitored to understand increased lumbar rotation to the dominant side in subjects with recurrent low back pain. The interactions between group and plane explain compensation strategies through increased lumbar rotation to the dominant side with decreased lateral bending of the upper thorax in subjects with recurrent low back pain. Highlights: The directional asymmetry should be carefully monitored to understand lateral bending task. The low back pain group increased lumbar rotation during lateral bending to the dominant side. The interactions between group and plane explain compensation in the low back pain group.